LEGAL PROVISION OF INFORMATION SECURITY AS A SUBJECT OF LEGAL INVESTIGATION - Кунєв, Юрій Дем’янович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
The purpose of the article is to formulate problems and determine the theoretical basis for their solution to the legal regulation of information security. Research methods: a comprehensive approach to creating a theoretical picture of the object and the application of the methodological scheme of «double knowledge» about the object as such and the knowledge that describes and depicts it; comparative legal and doctrinal knowledge of information law, as well as the method of generalization and modeling of new theoretical knowledge of information law. Results: problems of further development of legal provision of information security are identified and theoretical approaches for their solution are offered. To systematically solve the set of identified problems, it is necessary to implement the main task of legal support of information security to transform the content of information policy on information security as information legislation. The subject of legal support of information security is not only the activity itself but also the elements included in the systematic presentation of this activity, is the full scheme of cooperation of the activities of the participants in the implementation of such activities. Discussion: it is argued that the practical implementation of approaches based on the theoretical position: «legal organization of information security of the state» means streamlining, coordination of interconnected systems of information and information law, necessary for the acquisition of qualities and consolidation of laws that will ensure effectiveness and development of certain activities and the relevant social system. Prospective for the further development of scientific research is the practical implementation of approaches based on the theoretical position: "legal organization of information security of the state" means streamlining, harmonization of interconnected systems of norms and rules of law necessary to acquire qualities and and the development of certain activities and the corresponding social system and consists in the organization of systems of activities for the implementation of the rule of law and the organization of a system of norms that determine the activities.